Pattern and Knowledge of Wright′s Modification of Frankl′s Behavior Rating Scale Followed among Postgraduate Students of Pediatric Dentistry in Ahmedabad City - A Survey - Shital Kiran; Rohan Bhatt; Megha Patel; Nilay Shah (Advances in Human Biology, 2015)
Aim: To check the knowledge and technique of Wright′s modification of Frankl′s behavior rating scale among postgraduate students of pediatric dentistry in Ahmedabad city. Materials and Method: 21 postgraduate students studying in pediatric dentistry of different colleges from Ahmedabad city were selected. A questionnaire containing various questions regarding Wright′s modification of Frankl′s behavior rating scale was asked to fill. Result: The results suggested that they use this scale routinely and rate it properly but there are differences in timing of the rating. Conclusion: All Post Graduate students in pediatric dentistry from Ahmedabad city colleges use Wright′s modification of Frankl behavior rating scale routinely and correctly.